How corporate social responsibility and sustainable development functions impact the workplace: A review of the literature - Jean-Pascal Gond; Grace Augustine; Hyemi Shin; Alessandro Tirapani; Szilvia Mosonyi (International Labour Organization (ILO), 2022)
This report sets out to analyse the emergence and distinctive impact of corporate social responsibility and sustainable development (CSR/SD) functions and professionals within organizations. By evaluating the literature on this topic, it seeks to clarify how leveraging the already established CSR/SD functions and professionals across organizations can contribute to the International Labour Organization's (ILO) objective of achieving a future of work that provides decent and sustainable work opportunities for all. An extensive and integrative review of the academic literature was undertaken and an interview with a panel of academic experts conducted in order to highlight various aspects of CSR/SD functions and professionals. The focus was on three core topics: the embedding of CSR/SD functions and professionals (Topic #1); their role in managing stakeholder relations (Topic #2); and, more specifically, their contribution to the shaping of interactions with employees and trade unions (Topic #3). While CSR and SD have different historical roots, the two concepts overlap significantly. The umbrella term "CSR/SD" is therefore used throughout the report. "CSR/SD" itself is defined as encompassing corporate interactions with society and in particular with the multiple stakeholder groups from the corporate environment. "CSR/SD professionals" are defined as organizational actors either working within CSR/SD functions or whose role and activities at least have to do with managing CSR/SD issues. These functions are not a new phenomenon: a first wave emerged in the late 1960s and early 1970s. Renewed managerial interest in CSR/SD matters triggered the second wave in the 1990s, which was, paradoxically perhaps, strengthened by the 2008 financial crisis.
Keywords: 330; decent work; future of work; social dialogue; human resources development; management development; public private partnerships; sustainable development; business; corporate responsibility; enterprise development; multinational enterprises; business strategy; private sector; governance; research